Analysis of Different PWM Techniques for Enhanced Ultrahigh Gain Z-Network Topology - Vadthya Jagan; Bhavadish Chary Maheshwaram; Mallesh Usirikapally; Praveen Kumar Balachandran; B. Nagi Reddy; Sankeerthana Mettu; C. Dhanamjayulu; G. Arunkumar; K. C. Saranya; Baseem Khan (International Transactions on Electrical Energy Systems)
In these modern times, the Z-source inverters (ZSIs) have become a revolutionary invention ever since the year 2002. The pulse-width modulation (PWM) technique used for most of the ZSIs is simple boost control PWM (SBC-PWM), and the SBC-PWM implies for a greater voltage stress on the inverter bridge and provides less boost factor. Likewise, many topologies for the basic Z-source topologies are evolved, and different PWM techniques are applied to them such as maximum boost control (MBC), maximum boost control with third harmonic injection (MBC-THI), maximum constant boost control (MCBC), and constant boost control with third harmonic injection (CBC-THI). All these mentioned PWM techniques are compared, and the converter opted in this paper is an enhanced ultrahigh gain active-switched quasi-Z-source inverter (EUHG-qZSI). The comparisons discussed in this brief are bridge stress, voltage gain, and voltage boost variation under each control strategy implementation. The theoretical and simulation evaluation for the abovementioned findings is presented in this paper, and the best PWM among them is maximum boost control (MBC).